Pengaruh Beban Kerja dan Stres Kerja Terhadap Produktivitas Kerja Melalui Work-Life Balance di PT XYZ - Jon Edy; Soedjatmoko Soedjatmoko; Suripto Moh. Zulkifli; Suci Damayanti; Andi Rahman Hidayat (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study was conducted to examine the effects of workload and work-related stress on employee productivity, with work–life balance as an intervening variable, among Generation Z employees at PT XYZ. The study employed a quantitative associative approach, with data collected through a questionnaire distributed to 284 respondents selected using purposive sampling. Data analysis was performed using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, and path analysis. The results indicate that work load and work-related stress have a significant partial effect on work–life balance. Workload has a negative effect on work productivity, while work-related stress does not significantly affect employee productivity. Meanwhile, work-life balance was found to have a positive effect on work productivity. In its role as an intervening variable, work–life balance does not significantly mediate the effect of work stress on productivity, but it partially mediates the relationship between work load and work productivity. These findings indicate that proper work load management and efforts to maintain work–life balance are key factors in enhancing the productivity of Generation Z employees within the workplace at PT XYZ.